2021
DOI: 10.1186/s12884-020-03495-6
|View full text |Cite
|
Sign up to set email alerts
|

Progesterone levels predict pregnancy outcomes in individuals with fallopian tube associated infertility

Abstract: Background This study aimed at determining the predictive value of human chorionic gonadotropin and progesterone levels on pregnancy outcomes in patients receiving in vitro fertilization due to fallopian tube associated infertility. Methods We retrospectively analyzed the clinical data of 854 cycles due to fallopian tube associated infertility in vitro fertilization fresh embryo transfer. The clinical data had been collected from January 2010 to De… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 20 publications
0
1
0
Order By: Relevance
“…Furthermore a dataset demonstrated statistical detriment in live birth with P level as low as 0.7 ng/mL [15]. Previous studies also showed the effect of developmental stages of the embryo [13], the number of oocytes retrieved [16], cause of infertility [17] and different stimulation regimens [2] on the association of P levels and the likelihood of pregnancy. However, there is a missing puzzle of maternal age on such association.…”
Section: Introductionmentioning
confidence: 97%
“…Furthermore a dataset demonstrated statistical detriment in live birth with P level as low as 0.7 ng/mL [15]. Previous studies also showed the effect of developmental stages of the embryo [13], the number of oocytes retrieved [16], cause of infertility [17] and different stimulation regimens [2] on the association of P levels and the likelihood of pregnancy. However, there is a missing puzzle of maternal age on such association.…”
Section: Introductionmentioning
confidence: 97%